Pedagogika społeczna wobec Innego. Solidarność z Innym w kontekście globalizacji - Bielska, Ewa (Chowanna, 2019)
The subject of the analyses undertaken in this article is solidarity with the Other in global society. The first part of the article focuses on the status of the Other (the outline is based on the characteristics presented by Claude Lévi-Strauss, George Simmel, Zygmunt Bauman, Bernhard Waldenfels and Emmanuel Lévinas). The subject of the second part is the category of solidarity – its analysis has been made by referring to the sociological and axiological perspective. In the third part, which is a kind of summary, the ambivalence of the status of the Other in the context of globalization is presented.